Heritage of East Java: Konsep Visual pada Buku Ilustrasi Anak Tentang Pengenalan Pariwisata di Jawa Timur - Yudhistya Ayu Kusumawati; Victor Adiluhung Abednego (Jurusan Seni dan Desain, Fakultas Sastra, Universitas Negeri Malang, 2019)
Abstract: Tourism in Indonesia, especially East Java, has huge potential. For this reason, it needs to be introduced to the wider community. Introduction of tourism can be done early on through learning activities both formal and informal. Therefore, we need media that can be utilized and can be reached by all groups. One alternative media that can be applied is through illustration books. Books are media that can be interesting for children, especially because they are equipped with interesting illustrations. This research method uses descriptive qualitative method to explain the Heritage of Java design process. It is hoped that this book can increase user knowledge of tourism in East Java.Key Words: children book, illustrations, tourism, east java